Macronutrients as a Key Component of Healthy Nutrition for Pregnant and Lactating Mothers - Ernazarova, Shokhista Nazarovna (American Journal of Biology and Natural Sciences, 2026)
This article examines the importance of macronutrients in the healthy nutrition of pregnant and lactating mothers and emphasizes the need for their adequate presence in the daily diet. The study analyzes the obtained results and discusses possible approaches to overcome the identified deficiencies.